Prevalence and incidence of tick-borne diseases in smallholder farming systems in the western-Kenya highlands - Okuthe, O.S.; Buyu, G.E. (Elsevier, 2006)
The prevalence and incidences of tick-borne diseases (TBDs) infections in cattle were studied in the western-Kenya highlands. Serological tests, thick-blood and lymph-node smears were used to quantify TBDs during cross-sectional and longitudinal studies. Four hundred and eight and 192 (wet season) and 114 and 46 (dry season) cattle were bled for serology in the rural and peri-urban areas, respectively. Seroprevalences differed significantly between the two areas (p < 0.05). The cattle were monitored for 23 months (259,923 and 126,273 cattle days in the rural and peri-urban areas, respectively) from September 1996 to August 1998. The incidences of babesiosis, anaplasmosis and theileriosis were 0.42%, 4.64% and 4.92% and 1.45%, 32.11% and 39.05% in the rural and peri-urban areas, respectively. The difference in the incidence were significantly different for anaplasmosis and theileriosis (p < 0.05). The difference in disease frequencies in two areas in close proximity shows the importance of monitoring disease events in order to understand and advice farmers in different production and farming systems appropriately.